Diagnosing High School Students’ Misconceptions in Dynamic Electricity Using a Web-Based Four-Tier Test - Ernasari, Ernasari; Hermansyah, Moh Dimas Feri; Faresta, Rangga Alif (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study aimed to identify the conceptual understanding and types of misconceptions demonstrated by senior high school students in dynamic electricity using a web-based Four-Tier Diagnostic Test. The study employed a quantitative descriptive design involving 91 twelfth-grade students from a public senior high school in Jember, Indonesia, selected through purposive sampling. The validated instrument consisted of 30 items, each comprising a conceptual answer, answer-confidence rating, supporting reason, and reason-confidence rating. Expert validation yielded an overall feasibility score of 96%, indicating that the instrument was feasible for use. Students’ responses were classified as understanding the concept, not understanding the concept, misconception, or error based on the combinations of answers, reasons, and confidence levels. Across the student-item responses, 18% were classified as understanding the concept, 27% as not understanding the concept, 42% as misconceptions, and 13% as errors. Among the misconception-classified responses, theoretical misconceptions accounted for the largest proportion at 19.3%, followed by correlational misconceptions at 17.8%, calculation misconceptions at 16.9%, basic misconceptions at 16.4%, language-interpretation misconceptions at 15.3%, and systematic misconceptions at 14.3%. These findings show that students experienced substantial difficulties in understanding fundamental principles and connecting related concepts in dynamic electricity. The instrument can provide teachers with diagnostic information for designing targeted instructional and remedial activities.